Visualizing Research Trends on Culture Neuroscience (2008–2021): A Bibliometric Analysis - Xu, Han Qing; Chung, Chih-Chao; Yu, Cheng (Frontiers in Psychology, 2022)
Cultural neuroscience is new, import and interdisciplinary topic in the field of neuroscience in recent years. It plays a very important role in understanding interaction of cultural and biological factors across the life course. The purpose of this study is to help readers and potential researchers engaged in cultural neuroscience research to provide a comprehensive overview of the field. Using the core collection of web of science as the data source, a bibliometric analysis was performed on 113 literatures in the field of cultural neuroscience from 2008 to 2021. Network visualization software VOSviewer and ITGInsight were applied in the analysis for performance analysis and science mapping. Specifically, performance analysis include country, institution, author, paper, journal, and science mapping include collaboration network analysis, keyword network analysis, bibliographic coupling network analysis, and time series evolution analysis. The research results show that the usa is the most productive country, northwestern university is the most influential research institution, the most influential scholar is Chiao Jy, and the journal that has made the greatest contribution to publishing in the field of cultural neuroscience is " Social Cognitive and Affective Neuroscience ". Collaboration is the future development trend. The main research topics in the field of cultural neuroscience include neuroimaging and psychiatric diseases, theoretical methods, interdisciplinary, cultural differences(collectivism and individualism), and brain function. Among them, culture neuroscience, culture, and self are the research focuses and future research directions in the field of cultural neuroscience, and adolescent is the emerging research frontier.